Complement and organ transplantation - Sacks, Steven (Henry Stewart Talks, 2018)
Important barriers to successful transplantation, Tissue compartments affected by injury, Contribution of local synthesis of complement, C5a and C5b-9 dependent ischaemic renal tubule injury, Priming of the T cell response by C3a, C5a, Triggering complement activation on hypoxic cells